Urgensi Literasi Ekonomi Syariah Dalam Moderasi Beragama - Rohman, Asep; Juniawati, Mutmainah (Moderatio: Jurnal Moderasi Beragama, 2023)
The National Islamic Economic Literacy Index is 16.3% in 2021. As a concrete form of the above description, the existence of this conflict is due to other aspects such as political, social and economic factors, but an understanding of religion cannot be separated in minimizing this conflict. Sentiment from the emergence of various different religious understandings also triggers conflicts in society when there is a clash of religion, culture, social, economy and politics. Religious moderation is needed in the process of community literacy so that literacy has a positive impact on Islamic Economics. The concept and practice of Islamic Economics still requires development and is not free from deficiencies that make it not fully in accordance with Islamic law. Islamic Higher Education has a big role in the development of Islamic Economics. Education, research and service activities as part of the Tri Dharma of Higher Education make a very large contribution. Many findings and ideas about Islamic Economics were born in universities. Apart from that, there are also many new experts and practitioners of Islamic Economics who have emerged from universities. Economic justice in Indonesia can be realized by the spread of the Islamic economic system which has a moderate nature when compared to the capitalist system (dominance of capital owners) or socialist (state dominance). People who have good Islamic economic literacy (well literature) will behave in a moderate manner, namely accepting the idea of Islamic economics with its various shortcomings while still trying to push towards a better direction.